2010
DOI: 10.1128/aac.00966-09
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance in Haemophilus influenzae Respiratory Tract Isolates in Korea: Results of a Nationwide Acute Respiratory Infections Surveillance

Abstract: Antimicrobial susceptibility patterns and ␤-lactam resistance mechanisms of 544 Haemophilus influenzae isolates through the nationwide Acute Respiratory Infections Surveillance (ARIS) network in Korea during 2005 and 2006 were determined. Resistance to ampicillin was 58.5%, followed by resistance to cefuroxime (23.3%), clarithromycin (18.7%), cefaclor (17.0%), amoxicillin-clavulanate (10.4%), and chloramphenicol (8.1%). Levofloxacin and cefotaxime were the most active agents tested in this study. ␤-Lactamase p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
55
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 18 publications
6
55
3
2
Order By: Relevance
“…Compared with the report by Kim et al, 18 the proportion of IIa strains was markedly lower, and IIb strains were more prevalent in the nasopharyngeal BLNAR and BLPACR isolates (Table 1). However, the prevalence of IIb was similar to that noted by Bae et al 1 The most prevalent types of both BLNAR and BLPACR strains were also reported to be the most prevalent in a recent Portuguese study by Barbosa et al 2 (Table 1). The ftsI mutation groups of the BLPACR strains exhibited lower diversity than did those of the BLNAR strains, likely because the group of BLPACR strains originated from a small number of types (IIb and III) ( Table 1).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Compared with the report by Kim et al, 18 the proportion of IIa strains was markedly lower, and IIb strains were more prevalent in the nasopharyngeal BLNAR and BLPACR isolates (Table 1). However, the prevalence of IIb was similar to that noted by Bae et al 1 The most prevalent types of both BLNAR and BLPACR strains were also reported to be the most prevalent in a recent Portuguese study by Barbosa et al 2 (Table 1). The ftsI mutation groups of the BLPACR strains exhibited lower diversity than did those of the BLNAR strains, likely because the group of BLPACR strains originated from a small number of types (IIb and III) ( Table 1).…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies in South Korea showed that BLPAR strains were the most prevalent in the clinical setting, with BLNAR or BLPACR strains accounting for a smaller proportion. 1,18,19 However, in this study, both the prevalence of colonizing NTHi (34.2%) and rates of resistance (73.8%) were very high in the nasopharynx of hospitalized children with no infection history.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…A related cephalosporin, cefuroxime sodium, has been listed in the Catalogue of Basic Medicines of the State in China for the treatment of patients with infections of soft tissue, respiratory tract, urinary tract, bone and joint tissues [1][2][3] . With the merits of greater water solubility and reduced irritation to the veins, cefuroxime lysine may become a suitable substitute for cefuroxime sodium in these indications.…”
Section: Introductionmentioning
confidence: 99%